Comparison of Ultraviolet A/B and C Irradiation for Exosome Secretion Enhancement in HEK 293T Cell - Ching-Chih Chan; Pohao Lin; Yi Xian; Ruey-Hwang Chou; Yi-Jui Liu (Engineering Proceedings)
Exosomes, extracellular vesicles known for their stability, low immunogenicity, and excellent tissue penetration, are employed as delivery vehicles. These exosomes can traverse the tumor barrier and deliver therapeutic agents directly into pancreatic cancer cells. Targeted exosome vectors containing gene fragments to inhibit Kirsten rat sarcoma viral oncogene homolog (KRAS) activity are crucial for treating pancreatic tumors. Therefore, the content of the exosomes is critical. This study aims to compare the function of exosomes released by HEK-293T cells when exposed to ultraviolet A/B and ultraviolet C irradiation to determine its impact. HEK-293T cells were irradiated with ultraviolet A/B, and ultraviolet C for various indicated times, after which the cell count and exosome secretion were measured. Exosomes derived from HEK-293T cells were isolated through differential centrifugation and identified using four methods: cell counting, Bradford assay, nanoparticle tracking analysis (NTA), and Western blot analysis. Preliminary studies demonstrated that the cell count and Bradford assay expression were reduced in ultraviolet C compared to the control, with similar levels observed for ultraviolet A/B and the control. Exosome expression in Western blot analysis showed ultraviolet C, but a higher amount of ultraviolet A/B compared to the control. We introduce a comprehensive approach to ultraviolet irradiation, including ultraviolet A/B and ultraviolet C, which enhanced the secretion of exosomes by HEK-293T targeted vectors for KRAS inhibition in pancreatic cancer.